Advances in Solubility Enhancement Strategies for Poorly Water-soluble Drugs: A Comprehensive Review - Aman Suresh T.; Jeevan T.N.; Omkarswamy Maradimath (International Journal of Vaccines, 2024)
Solubility enhancement holds significant importance in the field of pharmaceutical research as it aims to augment the solubility and bioavailability of drugs that possess low solubility. Poorly soluble drugs pose a considerable challenge in drug development due to their tendency to display inadequate absorption, bioavailability, and therapeutic efficacy. The advancement of solubility enhancement techniques encompasses a wide range of approaches, including physical and chemical methods, as well as innovative technologies such as cyclodextrin complexes, co-crystals, nanoemulsions, amorphous solid dispersions, and supercritical fluid technology. The choice of solubility enhancement technique depends on the specific physicochemical properties of the drug and the desired formulation characteristics. However, it is important to consider the stability, toxicity, and pharmacokinetic profile of the drug when selecting a solubility enhancement strategy. Solubility enhancement is an ongoing challenge in drug development, but advancements in solubility enhancement techniques offer promising solutions for improving drug delivery and efficacy. This audit gives an idea of different dissolvability upgrade methods and their potential applications in sedate advancement. Extra examination and headway in this space might result within the creation of novel and upgraded choices
Keywords: bioavailability; cyclodextrin; hydrophobic drugs; nanosuspension; solubility